Frozen embryo transfers in a natural cycle: how to do it right. Issue 3 (14th June 2023) - Lawrenz, Barbara; Melado, Laura; Fatemi, Human M.
Abstract : Purpose of review: Assisted reproductive technology treatment has seen a significant shift from fresh to frozen embryo transfers (FET). Endometrial receptivity in the FET cycle can be achieved through a hormonal replacement cycle or a natural cycle, and the preparation approach has important implications on the pregnancy itself. In the natural cycle approach, planning of the embryo transfer timing might be challenging due to the need to identify ovulation correctly. Recent findings: Ovulation in a natural cycle is characterized by a luteinizing hormone surge, followed by the rise in progesterone (P4) levels, inducing secretory transformation. However, the luteinizing hormone surge can vary widely in its pattern, amplitude and duration and might not even result in the formation of a corpus luteum and P4 production. Monitoring of the luteinizing hormone surge using urinary luteinizing hormone kits might be a convenient approach, however, it is deemed unreliable and should be considered inadequate for securing the best outcome of a FET cycle. Summary: Endometrial receptivity depends on the duration of progesterone exposure to the adequately estrogenized endometrium. In a natural cycle endometrial preparation approach, correct planning for the embryo transfer timing should include the measurement of luteinizing hormone, estradiol and P4.